2012
DOI: 10.1016/j.jss.2011.11.1024
|View full text |Cite
|
Sign up to set email alerts
|

Increased JNK in Males Compared with Females in a Rodent Model of Abdominal Aortic Aneurysm

Abstract: Background In humans, there is a 4:1 male:female ratio in the incidence of abdominal aortic aneurysms (AAAs). c-Jun-N-terminal kinase (JNK) is an important upstream regulator of several enzymes involved in AAA formation, including the matrix metalloproteinases (MMPs). The purpose of this study was to determine if there is a gender difference between males and females in JNK during AAA formation. Materials and Methods Male and female C57/B6 mice underwent aortic perfusion with elastase or heat inactivated ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The protective effect of JNK inactivation can be explained by reducing the levels of the (active) proteases in the vessel wall and thus better preserved extracellular matrix. 24,36 Along this line, we observe a reduction of MMP2 and MMP9 protein in the vessel wall and AAA of Aza-treated mice.…”
Section: Discussionsupporting
confidence: 55%
“…The protective effect of JNK inactivation can be explained by reducing the levels of the (active) proteases in the vessel wall and thus better preserved extracellular matrix. 24,36 Along this line, we observe a reduction of MMP2 and MMP9 protein in the vessel wall and AAA of Aza-treated mice.…”
Section: Discussionsupporting
confidence: 55%
“…66 Testosterone upregulated JNK, a protein which stimulates apoptosis signaling pathway. 67 Androgens increased the incidence of AngII-induced AAA in mice and had the ability to stimulate MMP2 expression. 75 The effects of androgens on AAA formation include stimulation of components of the renineangiotensin system producing either increased synthesis or responsiveness to AngII.…”
Section: Discussionmentioning
confidence: 99%
“…DiMusto et al 67 examined sex differences in the c-Jun-N-terminal kinase (Jnk) production, an intracellular signaling molecule with important upstream regulation of several enzymes in AAA formation, inflammation, and cellular death, and found that significantly more Jnk1 or mitogenactivated protein kinase 8 (Mapk8) resulting in increase of pro-and active-MMP2 as well as pro-MMP9 in male versus female mice. In another study, the same group examined the role of plasminogen activator inhibitor 1 now known as Serpine1 in Serpine1 À/À mice and found that overexpression of Serpine1 prevented AAA development in female compared with male mice.…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 99%
“…Male gender is a well-known risk factor for AAA development (2426). Experiments with rodent AAA models have demonstrated that male animals develop a positive AAA phenotype compared with female animals (19, 2728). In the present study, gender-related differences in AAA phenotype between the two groups of mice on minimal phytoestrogen diet (M− versus F− group) were clearly demonstrated (109.3 ± 37.6% versus 52.9 ± 11.5%, P<0.001).…”
Section: Discussionmentioning
confidence: 99%